2012
DOI: 10.1016/j.pbb.2012.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Repeated cocaine administration in marmoset monkeys induces hypervigilance-related behaviors, but no changes in locomotion and cortisol levels

Abstract: Although cocaine induces several behavioral and hormonal effects, little is known about non-contingent repeated administrations in non-human primates. Therefore, we analyzed behavioral (locomotion, vigilance) and hormonal (cortisol) responses of adult black tufted-ear marmosets during repeated administrations and withdrawal trials. The subjects were divided into two groups (saline or cocaine 5mg/kg, ip) and submitted to nine treatment trials and four withdrawal trials in the absence of any treatment in an open… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
3
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 36 publications
5
3
0
Order By: Relevance
“…Rodents respond to repeated psychostimulant exposure with a hyperlocomotor effect that is: (1) very susceptible to behavioral sensitization (Vanderschuren and Kalivas, 2000); (2) inversely correlated with the initial cocaine response (Seymour and Wagner, 2008); (3) more pronounced in individuals that are highly explorative prior to drug exposure (Pierre and Vezina, 1997); and (4) strongly controlled by conditioned environmental stimuli (Mattson et al, 2008). Similar to previous reports from our group (Cagni et al, 2012(Cagni et al, , 2014Melamed et al, 2013), changes in locomotor activity were not detected in the marmosets. The hypervigilance effect was also not correlated with the initial response to cocaine or pre-drug vigilance, locomotion and exploratory levels, possibly an effect of the small sample size.…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…Rodents respond to repeated psychostimulant exposure with a hyperlocomotor effect that is: (1) very susceptible to behavioral sensitization (Vanderschuren and Kalivas, 2000); (2) inversely correlated with the initial cocaine response (Seymour and Wagner, 2008); (3) more pronounced in individuals that are highly explorative prior to drug exposure (Pierre and Vezina, 1997); and (4) strongly controlled by conditioned environmental stimuli (Mattson et al, 2008). Similar to previous reports from our group (Cagni et al, 2012(Cagni et al, , 2014Melamed et al, 2013), changes in locomotor activity were not detected in the marmosets. The hypervigilance effect was also not correlated with the initial response to cocaine or pre-drug vigilance, locomotion and exploratory levels, possibly an effect of the small sample size.…”
Section: Discussionsupporting
confidence: 85%
“…In humans, there is also a trend for the emergence of paranoid psychosis when higher doses of psychostimulants are used repeatedly (reviewed in Bradberry, 2007). As a matter of fact, it has been suggested that behavioral sensitization develops best in animals when moderately high doses are used (reviewed in Vezina and Leyton, 2009), with our present results and that of previous studies in NHPs corroborating this notion (Bradberry, 2007;Cagni et al, 2012Cagni et al, , 2014Melamed et al, 2013).…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations